Limited Substitutability, Relative Price Changes and the Uplifting of Public Natural Capital Values - Moritz A. Drupp; Zachary M. Turk; Ben Groom; Jonas Heckenhahn (CESifo GmbH, 2024)
While the global economy continues to grow, ecosystem services tend to stagnate or decline. Economic theory has shown how such shifts in relative scarcities can be reflected in project appraisal and environmental-economic accounting, but empirical evidence has been sparse to put theory into practice. To estimate the relative price change in ecosystem services that can be used for making such adjustments, we perform a global meta-analysis of contingent valuation studies to derive income elasticities of willingness to pay (WTP) for ecosystem services to proxy the degree of limited substitutability. Based on 861 income-WTP pairs from more than 400 studies, we estimate an income elasticity of WTP of around 0.8. Combined with estimates of good-specific growth rates, we estimate relative price change of ecosystem services of around 2.2 percent per year. In an application to natural capital valuation of forest ecosystem services by the World Bank, we show that public forest natural capital should be uplifted by around 60 percent. Our assessment of aggregate public natural capital yields a larger value adjustment of between 100 and 170 percent, depending on the discount rate. We discuss implications for policy appraisal and for improving estimates of natural capital in comprehensive wealth accounts.
Keywords: D61; H43; Q51; Q54; Q58; 330; willingness to pay; ecosystem services; income elasticity; limited substitutability; growth; relative prices; contingent valuation; forests; natural capital